Super-leading logarithms in pp → 2 jets - Thomas Becher; Patrick Hager; Giuliano Martinelli; Matthias Neubert; Dominik Schwienbacher; Michel Stillger (Journal of High Energy Physics)
Abstract Jet observables at hadron colliders feature “super-leading” logarithms, double-logarithmic corrections resulting from a breakdown of color coherence due to complex phases in hard-scattering amplitudes. While these effects only arise in high orders of perturbation theory and are suppressed in the large-N c limit, they formally constitute leading logarithmic corrections to the cross sections. We present the first analysis of the corresponding contributions to a hadronic cross section, including all partonic channels and interference effects. Interestingly, some interference terms in partonic q q ¯ $$ q\overline{q} $$ → q q ¯ $$ q\overline{q} $$ scattering are only linearly suppressed in 1/N c . Our results for the pp → 2 jets gap-between-jets cross section demonstrate the numerical importance of super-leading logarithms for small values of the veto scale Q 0, showing that these contributions should be accounted for in precision studies of such observables.